The Role Of The Head Of Public Health Graduate and Non Public Health Graduate Heads In Improving Managerial Abilities: Case Study of Puskesmas Bulu and Puskesmas Polokarto - Budhi Rahardjo; Suryo Ediyono; Nur Ani; Munika Saraswati (Universitas STRADA Indonesia, 2020)
This type of research is descriptive qualitative with a case study approach method. The subjects of this study were the Head of the Human Resources Division of the Sukoharjo Health Service, the Head of the public health center, and the public health center staff. Data collection techniques include direct observation, in-depth interviews, and documentation study. This study's data analysis stage in this study was data collection, data analysis, data reduction, data presentation, and conclusion drawing. The results of this study showed that the public health center headed by SKM graduates showed more role in managerial ability than the Head of Non-SKM public health center. Public health centers do not have to be led by a doctor, but SKM graduates can also show the public health center.